The Role of Waixenicin A as Transient Receptor Potential Melastatin 7 Blocker. (25th September 2012) - Kim, Byung J.; Nam, Joo H.; Kwon, Young K.; So, Insuk; Kim, Seon J.
Abstract Transient receptor potential melastatin 7 (TRPM7) plays a role in a number of physiological and pharmacological functions in variety of cells. The aim of this study was to clarify the role for TRPM7 channels and the effect of waixenicin A on the pacemaking activity of interstitial cells of Cajal (ICCs) and on the cell viability of the human gastric and breast adenocarcinoma cell lines, AGS and MCF‐7, respectively. Waixenicin A decreased the amplitude of pacemaker potentials in cultured ICC clusters and inhibited TRPM7 currents, but had no effect on Ca2+‐activated Cl− conductance (ANO1). Furthermore, waixenicin A was found to inhibit the growth and survival of AGS and MCF‐7 cells. These findings indicate that TRPM7 channel modulates intestinal motility and regulates the pathophysiology of human gastric and breast adenocarcinoma cells. These findings suggest that TRPM7 channel be considered a potential target for the treatment of gut motor disorders and gastric and breast cancer.